Peningkatan Kapasitas Produksi pada PT. Adicitra Bhirawa - Putri, Karine Santoso; Widyadana, I Gede Agus; Palit, Herry Christian (Jurnal Titra, 2015)
Currently, PT. Adicitra Bhirawa wants to increase their production capacity from 120 truck boxes per month into 250 truck boxes per month. The increasing of production capacity is applied by changing their production system from the piecework production system into line production system. The line production system is more efficient than the piecework production system in terms of the worker productivity. Line production system is designed using two heuristic methods of line balancing, Kilbridge-Wester and Helgeson-Birnie. The result shows Kilbridge-Wester gives the better result with 15 workstations. The proposed line production system can achieve the production target and increase the monthly worker productivity from 5.7 truck boxes/worker to 11.9 truck boxes/worker. A proposed plant layout is applied in order to support the new line production system.